Analisis Laporan Keuangan dalam Perspektif PSAK 101 - Widya Susanty (Journal Research of Economic and Bussiness, 2024)
This study aims to analyze the preparation of financial statements in the perspective of PSAK 101 in the Islamic Cooperative BMT Civil Society North Sumatra, BMT Al-Musabbihin, and BMT Mandiri Abadi Syariah in Medan City. Then perform analysis and factors that influence the preparation of financial statements according to PSAK 101. In fact, the preparation of financial statements in the Islamic Cooperative in preparing financial statements is still not optimal in the perspective of PSAK 101. This research is a qualitative research using interview, observation, and documentation data collection techniques. The method in this research is a qualitative exploratory by exploring the preparation of Islamic cooperative financial reports in the city of Medan according to PSAK 101.The results of this study indicate that in the preparation of financial reports for the Sharia Cooperative BMT Civil Society of North Sumatra, BMT Al-Musabbihin, and BMT Mandiri Abadi Syariah are still not according to PSAK 101. This is due to the lack of knowledge of the leaders' understanding of PSAK 101 and lack of training or information obtained regarding PSAK 101.